2016
DOI: 10.1590/0104-9224/si2103.10
|View full text |Cite
|
Sign up to set email alerts
|

Efeitos da Pulsação Ultrassônica da Corrente sobre a Geometria da ZF e ZAC na Soldagem Arco Submerso

Abstract: Este é um artigo publicado em acesso aberto (Open Access) sob a licença Creative Commons Attribution Non-Commercial, que permite uso, distribuição e reprodução em qualquer meio, sem restrições desde que sem fins comerciais e que o trabalho original seja corretamente citado. Resumo: O presente trabalho propõe investigar a aplicação da técnica de excitação ultrassônica do arco no processo SAW com o intuito de avaliar a influência dos principais parâmetros associados a pulsação da corrente, como a frequência e a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
1

Year Published

2018
2018
2021
2021

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 4 publications
0
2
1
Order By: Relevance
“…Table 3 presents the HAZ width variation as a function of the weld. Despite being in disagreement with the studies of Zhang et al [9], a decrease in the HAZ width on introducing ultra-high frequencies in the welding current was also observed by Voigt et al [11]. Also, the low-carbon-steel HAZ of all welds (including the reference) presented a significant increase in the percent of perlite compared to the region with no microstructural change.…”
Section: Low-carbon-steel Haz (Region 2)contrasting
confidence: 52%
See 1 more Smart Citation
“…Table 3 presents the HAZ width variation as a function of the weld. Despite being in disagreement with the studies of Zhang et al [9], a decrease in the HAZ width on introducing ultra-high frequencies in the welding current was also observed by Voigt et al [11]. Also, the low-carbon-steel HAZ of all welds (including the reference) presented a significant increase in the percent of perlite compared to the region with no microstructural change.…”
Section: Low-carbon-steel Haz (Region 2)contrasting
confidence: 52%
“…The justification for this phenomenon is given by Zhang et al [9]: When the current pulsed at ultra-high frequencies propagate through the matrix, it (the matrix) undergoes successive compression and expansion, creating a thermal gradient that accelerates the heat conduction and changes the temperature distribution, increasing the HAZ width. On the other hand, Voigt et al [11] observed a HAZ width decrease on introducing current pulsed at ultra-high frequencies in the welding of ASTM A36 steel joints through the SAW process.…”
Section: Introductionmentioning
confidence: 99%
“…The radial electromagnetic force is the key for the arc constriction and it reduces with decreasing root radius, which pushes the arc plasma to steady state. Anna applied the welding power in parallel with the ultrasonic excitation power in the submerged arc welding process to study the influence of the ultrasonic excitation frequency and current on the weld formation, and the research showed that the weld formation had no significant change under the set ultrasonic excitation parameters [19]. Zhang investigated the relationship between the ultrasonic excitation frequency and the ultrasonic excitation energy, and discussed the resonance phenomenon between the arc and ultrasonic [9].…”
Section: Introductionmentioning
confidence: 99%